Comparison of Corneal Thickness and Endothelial Cell Morphology in Myopic Patients with Daily Wear Hydrogel (Nelfilcon A) and Silicon Hydrogel (Lotrafilcon B) Contact Lenses: A Pilot Study - Cut Putri Samira; Tri Rahayu; Aria Kekalih (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2016)
Background: To compare corneal thickness and endothelial cell morphology in myopic patients wearing 1 month hydrogel conventional and silicon hydrogel contact lenses in daily wear.Methods: This is a prospective, single blind, randomized study. Seventeen (34 eyes) myopic patients were randomly assigned to receive either nelfilcon A or lotrafilcon B. Central corneal thickness (CCT), coefficient of variation (CV), and percentage of six-sided cell (6A) were examined using specular noncon robo Konan microscope. Changes in CCT, CV, and 6A were evaluated before contact lenses fitting as well as 1 week and 1 month after the treatment. Patients were also evaluated for any subjective side effects and complications during the treatment period. Results: There were 64.7% subjects with history of contact lens wearers and 52.9% of them was hydrogel wearers. After 1 month daily wear of nelfilcon A and lotrafilcon B, no statistically differences changes in CCT (p=0.285; Mann Whitney test), CV (p=0.587; unpaired t-test), and 6A (p=0.353; unpaired t-test). General linear model analysis in follow up evaluation with test of within subject effect revealed decreased in CCT (p=0.001) and CV (p=0.001), also increased in 6A (p=0.022) in all subjects.Conclusion: There were no statistically difference in CCT, CV, and 6A between daily wear of nelfilcon A and lotrafilcon B. Subjects with history of contact lens wearers gained advantages in oxygen availability, which decrease corneal thickness and improve endothelial cell morphology. Â Keywords: nelfilcon A, lotrafilcon B, simple myopic, corneal thickness, endothelial cell morphology